Analisis Pelaksanaan Manajemen Berbasis Sekolah Dalam Meningkatkan Hasil Belajar Siswa di SMA Negeri 1 Pampangan Kabupaten Ogan Komering Ilir - Suryawati, Suryawati; Nawawi, Effendi; Asteriniah, Femi (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2024)
The Implementation of School-Based Management is a policy that grants schools broad authority to determine their own needs and programs. This is done by utilizing available resources, both within and outside the school, to enhance the quality of education at SMA Negeri 1 Pampangan, Ogan Komering Ilir Regency, with the goal of improving student learning achievement. The research results from the Analysis of the Implementation of School-Based Management in Enhancing Student Learning Outcomes at SMA Negeri 1 Pampangan, Ogan Komering Ilir Regency, indicate that some aspects are functioning well, but there are also indicators that need improvement. One area that requires improvement is coordination with the community, especially parents or guardians. This is due to a lack of support from the school community and the public in supporting educational implementation. Furthermore, the facilities and resources for implementing School-Based Management are still insufficient. Some teaching aids, such as laboratory equipment and other teaching materials, are still lacking. Nevertheless, the school has made efforts to improve and upgrade their facilities and resources at SMA Negeri 1 Pampangan. This action is taken to ensure that facilities supporting the implementation of School-Based Management are adequately available at the school.